2016
DOI: 10.1111/1753-6405.12413
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation in the association between temperature and salmonellosis in NZ

Abstract: Objective: Modelling the relationship between weather, climate and infectious diseases can help identify high‐risk periods and provide understanding of the determinants of longer‐term trends. We provide a detailed examination of the non‐linear and delayed association between temperature and salmonellosis in three New Zealand cities (Auckland, Wellington and Christchurch). Methods: Salmonella notifications were geocoded to the city of residence for the reported case. City‐specific associations between weekly ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…En cuanto a los agentes causales, los resultados del estudio indican que el aumento de las temperaturas medias máximas semanales y del mes en curso están relacionadas con un mayor riesgo de presentación de casos de salmonelosis (36)(37)(38)(39).…”
Section: Resultados Por Grupos De Enfermedadesunclassified
“…En cuanto a los agentes causales, los resultados del estudio indican que el aumento de las temperaturas medias máximas semanales y del mes en curso están relacionadas con un mayor riesgo de presentación de casos de salmonelosis (36)(37)(38)(39).…”
Section: Resultados Por Grupos De Enfermedadesunclassified
“…Several studies have observed that the prevalence of Salmonella infections is strongly influenced by changes in ambient temperature [ 12 , 18 , 22 , 33 38 ], with higher rates often observed during the summer [ 12 , 22 , 39 ]. Multiple studies have also provided evidence that salmonellosis rates are positively associated with increased rainfall events [ 19 , 22 , 33 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have also provided evidence that salmonellosis rates are positively associated with increased rainfall events [ 19 , 22 , 33 , 40 ]. Moreover, there is growing evidence suggesting projected changes to climate [ 23 ] will affect the incidence of foodborne illness, including Salmonella infections [ 12 , 16 , 18 , 24 , 25 , 41 ]. Our findings provide further evidence that increases in ambient temperature and precipitation levels, particularly in the form of extreme events, are associated with increases in rates of salmonellosis.…”
Section: Discussionmentioning
confidence: 99%
“…This research employed a desktop‐based study to identify climate‐sensitive diseases of concern in the Torres Strait; these are defined as infections that may be affected by changing climatic conditions including local weather, air temperature, precipitation and humidity, water availability and food sources. Such conditions can change the distribution and breeding conditions of vector‐borne diseases, the population density or location of the animal species reservoir, and the disease transmission pathways 11,20 …”
Section: Methodsmentioning
confidence: 99%
“…This research responds to part of this call by identifying the present and future likelihood of increased occurrence of climate‐sensitive infectious diseases. It provides more detail to previous climate‐focused health research that noted changes in “temperature, humidity and rainfall can influence the transmission dynamics of infectious diseases” 6 (p561) and that climate change will compound determinants of infectious diseases, notably “globalisation, population growth and social and demographic inequalities” 11 . (p1) In responding to this call, this research addresses climate disruption through a localised perspective of the geographically vulnerable Torres Strait Islands.…”
mentioning
confidence: 99%